THE EFFECTIVENESS OF USING RECIPROCAL TEACHING STRATEGY TO IMPROVE READING COMPREHENSION OF THE TENTH GRADE STUDENTS OF SMA NEGERI 1 SOJOL - Enteding, Faradila; Thamrin, Nur Sehang; Wahyudin , Wahyudin; Usman, Sriati (e-Journal of ELTS (English Language Teaching Society), 2024)
This research aims to determine whether using the Reciprocal Teaching strategy can improve reading comprehension of the tenth grade studetns of SMA Negeri 1 Sojol. The researcher applied a quasi-experimental design by using purposive sampling to get the sample. The instruments of data collection were pre-test and post-test. The pre-test was used to measure students’ basic abilities and the post-test was used to measure the students’ improvement in reading comprehension after the researcher applied the treatment. The t-test was analyzed to compare the mean scores of the experimental group (77.23) and the control group (74.71). The significance level was 0.05 with 60 degree of freedom (df = 65). The result of data analysis indicated that the t-counted (6.54) is higher than the t-table (1.659). Based on the results, the hypothesis of this research is accepted. It can be concluded that using Reciprocal Teaching strategy is effective to improve reading comprehension of the tenth grade students of SMA Negeri 1 Sojol.